2021
DOI: 10.3390/foods10122991
|View full text |Cite
|
Sign up to set email alerts
|

The Aroma Fingerprints and Discrimination Analysis of Shiitake Mushrooms from Three Different Drying Conditions by GC-IMS, GC-MS and DSA

Abstract: The aroma fingerprints and discrimination analysis of shiitake mushrooms under different drying conditions were performed by GC-IMS, GC-MS, and descriptive sensory analysis (DSA) with advanced chemometric methods. Three samples (A, B, and C) were treated with varied drying degree and rate. The sample A and C were at the same drying degree and the sample B and C were at the same drying rate. The GC-IMS volatile fingerprints, including the three-dimensional topographic map, topographic map, and gallery plot, sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…The unidentified components were expressed by numbers, and some volatiles were identified with monomer (M) and dimer (D) in the fingerprint plot. This was also observed in GC-IMS fingerprints of shiitake mushrooms [ 23 , 24 ].…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…The unidentified components were expressed by numbers, and some volatiles were identified with monomer (M) and dimer (D) in the fingerprint plot. This was also observed in GC-IMS fingerprints of shiitake mushrooms [ 23 , 24 ].…”
Section: Resultsmentioning
confidence: 53%
“…Hou et al [ 23 ] successfully established the volatile fingerprints of shiitake mushrooms treated by HAD, VFD, VFD combined with HAD through GC-IMS. Chen et al [ 24 ] compared the effect of drying rate and degree in HAD treatment on flavor characteristic of shiitake mushrooms using GC-IMS and indicated that GC-IMS was an effective tool to discriminate different samples. Moreover, GC-IMS was also used to evaluate the volatiles of Cordyceps militaris chicken soup.…”
Section: Introductionmentioning
confidence: 99%
“…Fingerprints visually represent the results of the flavor measurement of samples. The VFC contents of CTLs can be compared visually and quantitatively via fingerprint analysis. , Figure shows the qualitative identification of 129 compounds. VFC contents are different in the CTLs of each region.…”
Section: Resultsmentioning
confidence: 99%
“…In order to better recognize the differences in flavor components in the four samples, the visual gallery plot was built according to the signal peak intensity of each compound ( Figure 3 b). Each row in the gallery plot represented all of the signal peaks selected in a sample, and each column represented the signal peaks of the same volatile substance in different samples [ 15 ]. From Figure 3 b, it can be seen that a total of 57 volatile compounds were successfully identified.…”
Section: Resultsmentioning
confidence: 99%
“…Gas chromatography ion migration spectrum technology (GC-IMS) with automatic headspace sampling (HS), as an emerging mass spectrometry technology, is gaining increasing popularity in the field of volatile flavor compound analysis [ 14 ]. In recent years, this technology has been successfully used to analyze the dynamic change in volatile compounds for mushrooms in the drying process and to distinguish the differences in flavor characteristics of mushrooms with different drying method treatments [ 15 , 16 ]. Compared with traditional spectrometry technology, HS-GC-IMS combines the advantages of both GC and IMS, such as high sensitivity, high accuracy, high efficiency, and low detection limits, which not only can acquire intuitive 2D and 3D maps, but can also increase the overall peak capacity, resolution, and qualitative analysis accuracy of compounds, especially for the analysis of some isomers [ 14 , 17 ].…”
Section: Introductionmentioning
confidence: 99%